GC-MS Analysis and In Vitro Cytotoxic Effects of Ocimum gratissimum (Lamiaceae) Volatile Oil and Thymol on Cancer Cells - Rose Osarieme Imade; Buniyamin Adesina Ayinde; Anam Alam (Mazandaran University of Medical Sciences, 2023)
Background: Cancer is one of the most prominent causes of death worldwide. Ocimum gratissimum Linn. (Lamiaceae) leaves are used in many countries as a spice or medicine.  Objectives: This study investigated the essential oil of the O. gratissimum leaves and its major constituent, thymol, for cytotoxic activity against breast (AU565) and cervical (HeLa) cancer cell lines.  Methods: Preliminary screening was carried out using bench-top assay methods for cytotoxicity involving the use of tadpoles of Raniceps raninus (10-40 μg/mL) and brine shrimp of Artemia salina (10-1000 μg/mL) and growth inhibition using radicle of Sorghum bicolor seeds (1-30 mg/mL). Antiproliferation was verified by 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay. Chromatographic separation of the oil resulted in fractions and sub-fractions, which were also subjected to biological testing. The components of the oil and active subfraction were further identified by gas chromatography-mass spectrometry (GC-MS).  Results: Remarkable cytotoxic activities were seen against R. raninus tadpoles and A. salina nauplii. Growth inhibitory activity on S. bicolor seed radicles was produced concentration-dependent. The subfraction possessed greater cytotoxic activity on the cell lines than the oil, with inhibitory action of +85.07% and +29.20% against AU565 and HeLa cells, respectively. Thymol was the major constituent of the oil (22.49%) and increased to 94.31% in the subfraction.  Conclusion: O. gratissimum volatile oil showed little inhibitory activity against AU565 and no inhibition on HeLa cells. However, its major component, thymol, demonstrated high potency, especially on the AU565 cell line, making it a good candidate for further studies.